2018
DOI: 10.1364/prj.6.000918
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible denaturation of DNA: a method to precisely control the optical and thermo-optic properties of DNA thin solid films

Abstract: The denaturation of double-stranded deoxyribonucleic acid (ds-DNA) has been well known to break nucleobase bonds, resulting in single-stranded deoxyribonucleic acid (ss-DNA) in solutions, which can recombine to form ds-DNA in a reversible manner. We developed an efficient process to irreversibly maintain various DNA denaturation levels in thin solid films in order to investigate the impacts of the denaturation on the optical properties of DNA films. By adding NaOH in an aqueous solution of salmon testis DNA, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 40 publications
2
10
0
Order By: Relevance
“…An increase of absorption in TSF compared to the solution precursors has also been observed in DNA. 4,6 In (Table 1), we also summarized how the thin lm thickness could be controlled by the tRNA concentration in the precursor solution. The lm thickness was exibly controlled in the range of 30 to 46 nm, and it monotonically increased with tRNA concentration.…”
Section: Absorption Spectra Of Trna Thin Solid Lmsmentioning
confidence: 99%
See 2 more Smart Citations
“…An increase of absorption in TSF compared to the solution precursors has also been observed in DNA. 4,6 In (Table 1), we also summarized how the thin lm thickness could be controlled by the tRNA concentration in the precursor solution. The lm thickness was exibly controlled in the range of 30 to 46 nm, and it monotonically increased with tRNA concentration.…”
Section: Absorption Spectra Of Trna Thin Solid Lmsmentioning
confidence: 99%
“…Deoxyribose nucleic acid (DNA) has recently shown prominent potential as a highly functional electro-optic material. 1,2 Thin solid lms (TSFs) made from either DNA aqueous solutions 3 or other organic solutions [4][5][6][7] have found unique optoelectronic applications. For instance, DNA-TSF has been used as an electron blocking layer in organic light-emitting diodes (OLEDs), 8,9 hydrogen-blocking layer in hybrid thin-lm transistors (TFTs), 10,11 a cladding layer in an optical waveguide modulator, 12 a sensing medium in optical sensors, 13,14 a nonlinear saturable absorber in femtosecond lasers, 3 and a radiation absorbing layer in solar cells, 15,16 to name a few.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…UV–VIS analysis indicates that there is no significant absorbance peak shift in DNA regardless of the existence or choice of solvent ( Figure 7 ). This is expected from previous research [ 20 , 30 , 39 ]; however, methanol, ethanol, and isopropanol exhibit different magnitudes in the peaks of DNA, and acetone solution is not graphed here since it exhibits a hard UV cutoff where the expected DNA peak is. Methanol and ethanol produce peaks of similar magnitude, while isopropanol produces a noticeably lower peak.…”
Section: Resultsmentioning
confidence: 61%
“…Therefore, a lower Std/Ave corresponds to higher uniformity. We observed that pure water-DNA solutions created large sample-to-sample variation, which can be caused by uneven distribution of the solution onto silicon wafers and minor misalignment of the wafers, and relative humidity can be a significant factor in film formation by spin coating [37][38][39]. The two data sets in Tables 1 and 2 demonstrate that pure aqueous-based…”
Section: Thin Films By Pure Water-dna Solutionsmentioning
confidence: 91%